2008
DOI: 10.1155/2008/293538
|View full text |Cite
|
Sign up to set email alerts
|

PPARα/γ‐Independent Effects of PPARα/γ Ligands on Cysteinyl Leukotriene Production in Mast Cells

Abstract: Peroxisome proliferator-activated receptor (PPAR) α ligands (Wy-14,643, and fenofibrate) and PPARγ ligands (troglitazone and ciglitazone) inhibit antigen-induced cysteinyl leukotriene production in immunoglobulin E-treated mast cells. The inhibitory effect of these ligands on cysteinyl leukotriene production is quite strong and is almost equivalent to that of the anti-asthma compound zileuton. To develop new aspects for anti-asthma drugs the pharmacological target of these compounds should be clarified. Experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…17,18 However, many recent reports demonstrate that TRG has PPARγ-independent activity by acting on uncharacterized off-targets. 19,20 To examine whether TRG activity in MCF7 cells is PPARγdependent, we exposed TRG-treated MCF7 parental cells to increasing doses of the PPARγ irreversible inhibitor GW9662. GW9662 inhibits PPARγ with an IC 50 of 3.3 nM.…”
Section: Resultsmentioning
confidence: 99%
“…17,18 However, many recent reports demonstrate that TRG has PPARγ-independent activity by acting on uncharacterized off-targets. 19,20 To examine whether TRG activity in MCF7 cells is PPARγdependent, we exposed TRG-treated MCF7 parental cells to increasing doses of the PPARγ irreversible inhibitor GW9662. GW9662 inhibits PPARγ with an IC 50 of 3.3 nM.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Zhang et al reported that fenofibrate induces PPARα-independent peroxisome proliferation in PPARα-null mice (Zhang et al 2006). Yamashita also showed that fenofibrate inhibits inflammatory cytokine production in PPARα-null mast cells (Yamashita 2008). More interestingly, Araki et al recently demonstrated, that some transcripts are induced in a PPARα-independent manner upon fenofibrate treatment (Araki et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that fenofibrate acts as a potent PPARα agonist (Gonzalez et al 1998;Staels et al 1998) and modulates the synthetic and catabolic pathways of triglyceride and cholesterol metabolism through selective activation of PPARα (Farnier 2008). However, several recent studies have also reported that fenofibrate plays a role in conditions under which PPARα is absent (Araki et al 2009;Yamashita 2008;Zhang et al 2006), suggesting fenofibrate exerts its physiological effects through PPARα-dependent and -independent mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…As described above, some causative substances of AERD may not strongly inhibit COX-1-dependent PG synthesis. We previously observed that the ligands of two well-known nuclear receptors, peroxisome proliferator-activated receptor (PPAR) α and γ, independently reduced cysLT release from stimulated RBL-2H3 mast cell line [58][59][60]. This may suggest the possibility of a role of some unknown target(s) of NSAIDs and other causative substances.…”
Section: Other Targets Of Aspirin the Bench-to-bed Approachmentioning
confidence: 95%
“…1b) as the NSAID to avoid unexpected protein acetylation by using aspirin [57]. We found that cysLT production increased when RBL-2H3 cells were pretreated overnight with dinitrophenol (DNP)specific immunoglobulin E (IgE) and then treated with DNPconjugated human serum albumin, creating a cellular model of type I allergy [58][59][60]. Treatment with indomethacin at concentration up to 3 μM did not cause dose-dependent changes of cysLT production, while there was almost 90% inhibition of PGD 2 production.…”
Section: Cellular Model Of Arachidonic Acid Metabolism Using a Culturmentioning
confidence: 99%